EROSION FEATURES ALONG CUA DAI BEACH, HOI AN CITY, QUANG NAM PROVINCE, VIETNAM - Mau, Le Dinh; Trung, Pham Ba; Binh, Tran Van (Vietnam Journal of Marine Science and Technology, 2019)
Hoi An is a famous tourist city in Central Vietnam with Cua Dai beach which is a long beautiful swimming beach. In recent years, tourism of the city is developing very fast. The southern part of Cua Dai beach was covered by many resorts which were located close to the beach and protected by hard structures such as seawall, revetment, groin,… At present, all properties closed to the beach and hard protection structures of resort system were destroyed by wave action. And the northern part of Cua Dai beach (public beach) was seriously eroded and has been protected by “Soft structure”. Cua Dai coast erosion problem becomes the hot topic in communication system from central to local governments and it becomes the big concern of Vietnamese and international scientists. This paper presents the initial study results of Cua Dai beach erosion features. Study results show that Cua Dai beach erosion/deposition phenomenon occurred for a long time but the rate of accretion was larger than that of erosion. From the year of 2000 to present the rate of erosion was larger than that of accretion. The main causes of Cua Dai beach erosion are the interaction between hard protection structures and wave action, dredging operation in Thu Bon river mouth... which reduced the longshore sediment transport rate from Thu Bon river mouth to eroded beach.